2021
DOI: 10.3390/ijms22168491
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cachexia: Its Mechanism and Clinical Significance

Abstract: The term “cachexia” is derived from the Greek words kakos (bad) and hexis (habit). Cachexia is a malnutrition associated with chronic diseases such as cancer, chronic heart failure, chronic renal failure, and autoimmune diseases, and is characterized by decreased skeletal muscle mass. Cancer cachexia is quite common in patients with advanced cancer. Weight loss is also a characteristic symptom of cancer cachexia, along with decreased skeletal muscle mass. As nutritional supplementation alone cannot improve cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(109 citation statements)
references
References 112 publications
(177 reference statements)
3
103
0
3
Order By: Relevance
“…The ORs for the OS of GPS 1 and GPS 2 in this study were 1.953 (p = 0.0147, GPS 0 as a reference) and 3.460 (p < 0.0001, GPS 0 as a reference), which were consistent with previous reports [28,29,35]. Although BMI was not significant for the OS in our results, body weight loss was an important factor associated with cancer cachexia [10]. In our cohort, 86 patients (20.4%) had BMI < 18.5 kg/m 2 (underweight).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The ORs for the OS of GPS 1 and GPS 2 in this study were 1.953 (p = 0.0147, GPS 0 as a reference) and 3.460 (p < 0.0001, GPS 0 as a reference), which were consistent with previous reports [28,29,35]. Although BMI was not significant for the OS in our results, body weight loss was an important factor associated with cancer cachexia [10]. In our cohort, 86 patients (20.4%) had BMI < 18.5 kg/m 2 (underweight).…”
Section: Discussionsupporting
confidence: 91%
“…Malnutrition, reticence, advanced malignancy burden, and persistent inflammatory condition often identified in patients with gastrointestinal disorders are typical clinical characteristics associated with sarcopenia [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Patients with advanced cancer are prone to muscle protein loss due to muscle proteolysis-inducing factors and inflammatory cytokines released by the cancer cells [ 10 ]. In addition, psychological anxiety and side effects of treatment for the underlying malignancies can lead to a loss of appetite, and numerous previous studies have reported that sarcopenia is an adverse predictor in patients with advanced cancer [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ROC analyses both for mild or more severe malnutrition and for the moderate or more severe malnutrition, CRP had the highest AUC. Proinflammatory cytokines include IL-1β, IL-6, TNF-α, and IFN-γ, and they cause decreased appetite and increased energy expenditure, which can be related to our results [36]. Cachexia is a common form of disease-related malnutrition associated with inflammation and loss of skeletal muscle mass.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, lymphocytes are responsible for the immune function of the host, and a decrease in lymphocytes can damage the host’s anti-tumor immunity and worsen the prognosis [ 23 ]. Thus, in advanced cancer, NLR reflects the balance between tumor promotion and anti-tumor immune status [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%